THE PRINCIPLE OF COOPERATION IN COMMUNICATION AND A CRITICAL VIEW OF THE DOCTRINE OF P. GRACE - Begmatova, Rano (Журнал иностранных языков и лингвистики, 2022)
The article is devoted to the analysis of the essence of the concepts of "cooperation", a review of the functioning of these terms in modern linguistics.